TINDAK TUTUR EKSPRESIF DALAM PERCAKAPAN DI KALANGAN REMAJA DI KELURAHAN KALABBIRANG KABUPATEN TAKALAR - Nur Fatimah; Syamsudduha; Fitri, Sakinah (Journal Studies in Indonesian Language and Literature, 2024)
The aim of this research is to determine the form and function of expressive speech acts in conversations among teenagers in Kalabbirang sub-district, Takalar district. The aim of this research is to determine and describe the form and function of expressive speech acts in conversations among teenagers in Kalabbirang sub-district, Takalar district. It is hoped that this research can become a very important reference and increase insight in the context of improving regional language learning, especially pragmatics in determining the form and function of speech acts. The data source in this research is conversations among teenagers in Kalabbirang Village, Takalar Regency. The method used in this research is the listening method, this method describes the forms and functions contained in conversations among teenagers in Kalabbirang Village, Takalar Regency. Based on research conducted, 6 forms and functions were found in conversations among teenagers in the Kalabbirang subdistrict, Takalar district, which included saying thank you, congratulating, apologizing, blaming, praising and sarcasm.